Genre-Based Approach Listening Instruction: A Case Study in a Blitar Senior High School - Cahya, Anggun Nilam; Sari, Hesty Puspita; Sutanti, Nita; Primasari, Yusniarsi (Proceeding International Conference on Education, 2024)
This qualitative case study investigates the implementation of the Genre-Based Approach (GBA) in teaching listening skills to 10th-grade students at SMAN 1 Sutojayan, Indonesia. Employing observations and interviews, the research explores the effectiveness of GBA in a practical classroom setting. Findings indicate that while GBA provides a sound theoretical framework, its success hinges on comprehensive preparatory activities, particularly pre-listening tasks that build vocabulary and contextual understanding. The study highlights the need for differentiated instruction to address varying student proficiency levels and recommends targeted pre- and post-listening activities to boost comprehension and engagement. The outcome of this research is a framework for teaching listening using the Genre-Based Approach. This framework can serve as a guide for applying the same method in other schools. Overall, the research underscores the potential of GBA in enhancing listening skills, suggesting that its effectiveness can be significantly amplified through meticulous implementation and support. Future research should investigate additional strategies to further tailor GBA to diverse student needs and promote overall engagement in listening